A Low-Complexity Iterative Phase Noise Tracker for Bit-Interleaved Coded CPM Signals in AWGN - Noels, N.; Moeneclaey, M.; Simoens, F.; Delaruelle, D. (IEEE transactions on signal processing, 2011)
This paper considers iterative detection of bit-interleaved coded continuous phase modulation in the presence of both phase noise (PN) and additive white Gaussian noise (AWGN). The proposed receiver iterates between a detection module and an estimation module. The detection module operates according to the sum-product algorithm and the factor graph framework in order to perform coherent maximum a posteriori bit detection in AWGN, using a PN estimate provided by the estimation module. The latter module, which results from the expectation-maximization algorithm for maximum likelihood estimation of the unknown PN samples, is implemented as a smoothing phase-locked loop that uses soft decisions provided by the detector. The separation between the detection and the estimation modules allows the use of an off-the-shelf (coherent) bit detector. The technique is further characterized by a very low computational complexity, a small error performance degradation and a small number of overhead symbols.